2023
DOI: 10.21203/rs.3.rs-2661673/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inequalities of Inpatient Health Services Utilization for the Middle-Aged and Elderly with Multiple Chronic Conditions in China

Abstract: Background Despite growing evidence of health inequalities, equity of inpatient health service utilization(IHSU) among middle-aged and elderly people with multiple chronic conditions(MCCs) have received little attention. Therefore, this study aims to access the inequities of IHSU among middle-aged and elderly people with MCCs in China, and determine the contributing social factors and their influences by using the national data. Methods This study used two cross-sectional data from the 2013 and 2018 China He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In this study, we identified 14 common chronic diseases based on the most frequently mentioned diseases for multimorbidity measures in previous studies (7,(9)(10)(11). Hypertension was defined as an average SBP of ≥140 mmHg and/or an average DBP of ≥ 90 mmHg, or self-reported hypertension history.…”
Section: Definition and Measurement Of Multimorbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we identified 14 common chronic diseases based on the most frequently mentioned diseases for multimorbidity measures in previous studies (7,(9)(10)(11). Hypertension was defined as an average SBP of ≥140 mmHg and/or an average DBP of ≥ 90 mmHg, or self-reported hypertension history.…”
Section: Definition and Measurement Of Multimorbiditymentioning
confidence: 99%
“…A large body of literature has revealed the prevalence and patterns of multimorbidity among adults in China. The prevalence of multimorbidity ranges widely from 4.8 to 90.5% (7)(8)(9)(10) because of variance in aspects such as geographical environments and the definitions and measurements of disease (11,12). In general, people who are older, female, or living in northern areas have a higher prevalence of multimorbidity (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the comorbidity rate of hypertension and diabetes in MPCDs over 40 years old was 79.9%, much higher than the chronic disease comorbidity rate of 41% in middle-aged and elderly in China. 35 This difference may be due to data sources or the types of chronic diseases investigated, but it also reflects the overall poor health status of MPCDs. The prevalence of MPCDs within two weeks was 60.62% (5278 /8706).…”
Section: Prevalence and Consultation Rate Of Mpcdsmentioning
confidence: 99%